PPO.52 Cervical Suture – A Single Centre Experience of Comparative Efficacy Between Elective, Semi-Elective and Rescue Sutures. (9th June 2014) - McPherson, KC; Trimble, A; Doherty, G; Owen, P; Ledingham, MA
Abstract : Introduction: Preterm delivery is the leading cause for infant mortality and morbidity. Cervical incompetence is a recognised cause for both extreme prematurity and second trimester loss. Use of cervical sutures may reduce these risks. We present an assessment of cervical suture use in a busy regional centre. Method: Women who had an attempted cervical suture insertion were identified from theatre records from 2010–2013. Case notes were reviewed retrospectively and index pregnancy was identified as the first attempt to insert a cervical suture. Cervical sutures were categorised as "elective" when there was no evidence of cervical change, "semi-elective" when cervical sutures were attempted following shortening / funnelling of the cervix was identified on transvaginal ultrasound, "rescue" when cervical dilatation was said to have occurred. Results: 26 patients were identified. 25 sutures were attempted in singleton pregnancy and 1 in a DCDA twin pregnancy. 10/25 (40%) of women had a previous history of preterm birth. Elective cervical sutures were used in 11/26 (42.3%) cases, Semi-elective sutures in 7/26(26.9%) cases, Rescue sutures in 8/26 cases (30.8). 19/26 (73.1%) of pregnancies resulted in a live birth, of which 11/11 (100%) Elective sutures, 6/7 (85.7%) of Semi-elective sutures and only 2/8 (25%) Rescue sutures resulted in live birth (p 0.0005). Conclusion: Survival in the "rescue" cervical suture group was significantly poorer in comparison to both "elective" and "semi-elective" groups. This data supports the use of early cervical length screening in high risk cases. Further studies are required to identify optima timing of serial cervical length.